Genotype and environmental interaction of certain indices of dormancy in winter wheat - A. Binek; M. Moś (Plant, Soil and Environment, 2005)
On the basis of five statistical parameters the stability of three dormancy indices, i.e. germinability, germination rate and dormancy index, has been determined 10 days after harvest at temperatures of 25°C. The object of the research included seeds of 12 winter wheat cultivars harvested in the years 1997-2003. In spite of significant genotype x environmental interactions accounting for 23.8-50.6% of the total variation, a significant differentiation between all the indices was found. Among the investigated cultivars a low level of dormancy was observed in the cultivars Wanda, Juma and Begra (germinability 83-92%, dormancy index 7.7-9.5), while evident dormancy was found in the cultivars Elena, Izolda, Almari, Mikon and Kobra (germinability 44-58%, dormancy index 21.3-32.2). The cultivars showing deep dormancy were characterized by lower stability of both the indices. The cultivars strongly reacting to the seasonal variation (b1 > 1), in respect of the three indices, were Sakwa, Kobra, Mikon and Elena. High consistency of the stability parameters was found between ecovalence and mean square of deviations from regression (r = 0.87**-0.98**) and between the linear regression coefficient and the coefficient of determination (r = 0.69*-0.86**).